Analisis Kebijakan Pajak Digital dan Dampaknya Terhadap Kepatuhan UMKM Di Indonesia: Studi Literatur dan Analisis Kebijakan - Ros Nirwana; Suzi Suzzana; Hasdi Suryadi; Jakiroh; Endah Sri Bintari (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2026)
Tax compliance among Micro, Small, and Medium Enterprises (MSMEs) in Indonesia remains a significant challenge, despite the implementation of various digital tax policies. The gap between administrative compliance and substantive compliance indicates that tax digitalization has not been fully effective in fostering sustainable compliance. This study aims to analyze digital tax policies and their impact on MSME tax compliance using the perspectives of Tax Behavior Theory, Tax Compliance Theory, and E-Government Theory. This research employs a qualitative approach using literature review and policy analysis of relevant digital tax regulations, including Government Regulation No. 23 of 2018 and Ministry of Finance Regulation No. 62/PMK.03/2020. Secondary data were collected from academic journals, books, regulatory documents, and official reports, and analyzed using thematic analysis through stages of coding, categorization, and interpretation. The findings indicate that MSME tax compliance in the digital era is influenced by the interaction of behavioral, regulatory, and technological factors. Digital systems such as e-Filing and e-Billing have improved administrative compliance by enhancing efficiency and ease of use. However, low tax and digital literacy, limited technological infrastructure, and system complexity remain major barriers. In addition, risk-based supervision strengthens enforced compliance, but may reduce taxpayer trust if not accompanied by high-quality public services. This study concludes that the effectiveness of digital tax policies depends not only on technological transformation but also on the balance between behavioral factors and compliance approaches based on trust and power. Therefore, a more comprehensive strategy is required, including improving literacy, simplifying tax systems, and enhancing transparency and public services to promote sustainable MSME tax compliance.